Psychological, Biological and Social Variables Involved in Tobacco Use among Adolescents - Ana María Zurbarán Hernández; Teresa Rodríguez Rodríguez; Arasai Zurbarán Hernández; Caridad Hernández Abreus (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Tobacco use is a risk factor that predisposes to various diseases, known as chronic non-communicable diseases. It is a global health problem that causes up to 5 million deaths a year. Adolescence is the time where smokers mainly start, therefore preventive work is necessary from the early stages of life. A bibliographic review is carried out on the main psychological, biological and social variables that intervene in the consumption of tobacco in adolescents, in addition to the different theoretical models or psychological schools that have addressed this problem and have suggested modes of action, to face this harmful habit. An exhaustive search was carried out on the subject, for this the specialized bibliography was consulted, including magazine articles, books and others, accessed through the main information managers, obtaining a clarification about the main aspects involved in the acquisition of addictive behavior by sensitive populations.